Robotic Colorectal Resection With and Without the Use of the New Da Vinci Table Motion: A Case-Matched Study. (June 2018) - Palmeri, Matteo; Gianardi, Desirée; Guadagni, Simone; Di Franco, Gregorio; Bastiani, Luca; Furbetta, Niccolò; Simoncini, Tommaso; Zirafa, Cristina; Melfi, Franca; Buccianti, Piero; Moglia, Andrea; Cuschieri, Alfred; et al.
Background. The da Vinci Table Motion (dVTM) is a new device that enables patients to be repositioned with instruments in place within the abdomen, and without undocking the robot. The present study was designed to compare operative and short-term outcomes of patients undergoing colorectal cancer surgery with the da Vinci Xi system, with or without use of the dVTM. Methods. Ten patients underwent robotic colorectal resection for cancer with the use of dVTM (Xi-dVTM group) between May 2015 and October 2015 at our center. The intraoperative and short-term clinical outcome were compared, using a case-control methodology (propensity scores approach to create 1:2 matched pairs), with a similar group of patients who underwent robotic colorectal surgery for cancer without the use of the dVTM device (Xi-only group). Results. Overall robotic operative time was shorter in the Xi-dVTM group ( P = .04). Operations were executed fully robotic in all Xi-dVTM cases, while 2 cases of the Xi-only group required conversion to open surgery because of bulky tumors and difficult exposure. Postoperative medical complications were higher in the Xi-only group ( P = .024). Conclusions. In this preliminary experience, the use of the new dVTM with the da Vinci Xi in colorectal surgery, by overcoming the limitations of the fixed positions of the patient, enhanced the workflow and resulted in improved exposure of the operative field. Further studies with a greater number of patients are needed to confirm these benefits of the dVTM-da Vinci Xi robotically assisted colorectal surgery.